Age does not influence efficacy of ramucirumab in advanced gastric cancer: Subgroup analyses of REGARD and RAINBOW. Issue 4 (1st February 2018) - Muro, Kei; Cho, Jae Yong; Bodoky, Gyorgy; Goswami, Chanchal; Chao, Yee; dos Santos, Lucas V; Shimada, Yasuhiro; Topuzov, Eldar; Van Cutsem, Eric; Tabernero, Josep; Zalcberg, John; Chau, Ian; et al.
Abstract: Background and Aim: REGARD and RAINBOW were global, phase 3, randomized, double‐blind trials of second‐line ramucirumab for metastatic gastric or gastroesophageal junction adenocarcinoma. Exploratory subgroup analyses were described to assess the efficacy and safety of ramucirumab in REGARD and RAINBOW in young (≤ 45 and < 65 years) and elderly (≥ 65, ≥ 70, and ≥ 75 years) patients. Methods: Patients were randomized 2:1 to receive ramucirumab plus best supportive care or placebo plus best supportive care (REGARD) or 1:1 to ramucirumab plus paclitaxel or placebo plus paclitaxel (RAINBOW). Subpopulation Treatment Effect Pattern Plots assessed efficacy and adverse events by age groups for ramucirumab versus placebo. Results: The hazard ratios (HRs) for overall survival favored treatment with ramucirumab: REGARD ≤ 45 years (HR: 0.59, 95% confidence interval: 0.27–1.26), < 65 years (0.80, 0.59–1.10), ≥ 65 years (0.72, 0.48–1.08), ≥ 70 years (0.73, 0.44–1.23), and ≥ 75 years (0.59, 0.25–1.37); and RAINBOW ≤ 45 years (0.56, 0.33–0.93), < 65 years (0.78, 0.63–0.97), ≥ 65 years (0.88, 0.66–1.18), and ≥ 70 years (0.88, 0.60–1.28). The exception was elderly patients aged ≥ 75 years in RAINBOW (0.97, 0.47–2.01); however, patient numbers were low in this subgroup ( n = 36). Similar findings were observed for progression‐free survival, for which HRs numerically favored ramucirumab‐treated patients. Adverse events (including grade ≥ 3) were not associated with age. Conclusions: In comparison with placebo, ramucirumab conferred improvements in efficacy across age groups with a tolerable safety profile. Despite some limitations, these exploratory analyses support the use of ramucirumab in advanced gastric cancer, irrespective of age.